Varus external rotation stress test for radiographic detection of deep deltoid ligament disruption with and without syndesmotic disruption: A cadaveric study - John E. Femino (2018)
Background: External rotation stress is used intraoperatively for diagnosing medial ankle and syndesmotic instability in rotational ankle fractures after reduction and fixation of the fibula. However, external rotation includes hindfoot, midfoot, and ankle motion. The purpose of this study was to determine the effect of hindfoot positioning when using the external rotation stress test. Isolated deep deltoid ligament (DDL) instability and combined DDL and syndesmotic instability were modeled. An intact fibula was used as a surrogate for an anatomically fixed fibula fracture. Methods: Six cadaver specimens with full-length tib-fib articulations were used. Specimens were fixed into a Taylor Spatial Frame (Smith & Nephew, Memphis, TN) with 4 to 5 points of fixation in the tibia and the foot. Specimens were mounted in ankle and foot neutral position. Metal markers were placed at the medial gutter and syndesmosis. Anteroposterior (AP) and mortise radiographs were obtained in 3 positions: neutral hindfoot, valgus external rotation stress, and varus external rotation stress. For both valgus and varus external rotation stress, the frame was loosened and stressed to a hard end point and then locked. Three modes were studied: intact ligaments, DDL transected, and DDL+ syndesmosis transected. Digital radiographs were used to measure the displacement of the markers. Results: The varus external rotation stress test demonstrated significant widening of the medial gutter in specimens with isolated DDL instability, in both AP (P = .01) and mortise (P = .02) views. Both maneuvers demonstrated significant medial gutter widening with combined DDL and syndesmosis disruption (P ≤ .01), although the varus external rotation stress test produced nearly twice as much displacement (10.7 vs 5.4 mm). Syndesmotic widening was not significant with either maneuver. Conclusions: Varus external rotation stress was more effective than valgus external rotation stress in demonstrating displacement of markers at the medial gutter and on AP and mortise radiographs for both DDL and DDL with syndesmotic instability. Clinical Relevance: These findings may lead to improved clinical detection of rotational ankle instability from combined DDL and syndesmotic disruption, which may affect decision making for using syndesmotic fixation when using intraoperative stress fluoroscopy images. Occult DDL instability may be underdiagnosed, and this may affect future directions of the treatment of rotational ankle fractures and severe sprains. © The Author(s) 2013.